Development of SCAR marker for screening Sigatoka-leafspot resistance in banana genotypes - Das, Tanusree; Mondal, Subhasish; Mishra, Dilip K.; Bhattacharyya, Somnath (The Indian Journal of Genetics and Plant Breeding, 2016)
Sigatoka leaf spot is a major fungal disease of banana worldwide, particularly, in pacific island, from where this pathogen originated. Not so many resistant genotypes are reported against this. Initially, RAPD fragments correlating with lower percentage of disease index (PDI) were identified involving fifteen banana cultivars collected from diverse zone of West Bengal. Four correlating RAPD fragments from each two independent genotypes were cloned, sequenced and submitted into GenBank. It had been observed that sequence information was dissimilar even though same RAPD primer amplified equal sized amplicon from two different varieties. Even fragment from two different clones of a variety, was also dissimilar. Based on sequence information, eight pairs of SCAR primers were designed. Only one SCAR primer based on the sequence of OPA13640 from Kanthali Clone1 showed reproducible dominant banding pattern like RAPD. Identified SCAR marker when validated among additional 26 diverse genotypes, collected across India, showed strong correlation with the Sigatoka resistance lines. SCAR markers identified and validated in this study will be useful in screening Sigatoka resistance lines in future banana breeding program.